Risk management for financial institutions : applying cost-effective controls and procedures - Thornhill, William T. (Rolling Meadows, Ill. : Bankers Publishing, 1990)
In a competitive environment where risk abounds and profits are tough to achieve, financial institutions cannot afford to be unprotected. This book provides the answers bankers need to identify and control the key risk factors they face, both internally and externally. Focusing on examples and case studies of actual situations, the book shows bankers how financial performance is impacted by administrative, operational and insurance risk management. Bankers will find practical answers to their questions, such as how to attract and retain good outside directors in these times of liability suits; how safe are automatic teller machines and are customers in danger; are internal controls against check kiting adequate; and is there adequate protection against computer viruses?
Includes bibliographical references and index.
aia 05/09/2016
Loans
Keywords: Risk management; Financial institutions; Finance $1 (BRisks $1 (BManagements; Banking--- Operational Research; Banks and Banking; Operational Research